Antidiabetic activity of leptospermum flavescens in alloxan - induced diabetic rats / Asmawati Abd Rahim - Asmawati, Abd Rahim (2012)
The phytochemical analysis was carried out using hexane, chloroform and water extraction of the leaves and stems of L. flavescens. The detection methods used were thin layer chromatography (TLC), high performance liquid chromatography (HPLC) and liquid chromatography mass spectrometry combined with mass spectrometry (LCMS/MS). The TLC of all extracts using three solvents screened for flavonoids, alkaloids, saponins, terpenoids and essential oils. The HPLC have been identified quercetin, gallic acid and tannic acid using authentic standards. The HPLC chromatograms were poorly separated and not very convincing to confirm the three compounds. However the liquid chromatography mass spectrometry combined with mass spectrometry (LCMS/MS) has successfully identified 13 metabolites.